PILOKARPIN UNTUK MEMBUAT HEWAN MODEL EPILEPSI LOBUS TEMPORALIS - Diah Kurnia Mirawati,* Suroto,* Brian Wasita,** Junaidi Khotib*** (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION TEMPORAL LOBE EPILEPSY IS THE MOST COMMON TYPE OF EPILEPSY IN ADULT UNFORTUNATELY MECHANISM OF THIS DISEASE REMAINS UNCLEAR THEREFORE IT NEEDS MANY RESEARCHES TO UNFOLD THIS MYSTERY RESEARCH IN HUMAN OFTEN FACES OBSTACLES ESPECIALLY IN ETHICS SO ANIMAL MODEL IS NECESSARY TO REPLACE HUMAN ROLE IN THE STUDY OF PATHOPHYSIOLOGY OF THE DISEASE